Microleakage of Class V compomer resin restorations after conventional diamond bur and Er, Cr:YSGG laser preparation - Fatih Oznurhan; İpek Arslan; Ozgul Baygin; Tamer Tuzuner (Cumhuriyet University, 2012)
Objectives: The aim of this study was to compared the microleakage of Class V compomer resin restorations prepared by Er,Cr:YSGG laser or conventional diamond bur. Materials and Methods: Ninety sound primary molar teeth were randomly assigned to the six study groups, pretreated as follows: Group1:2W-10Hz Er,Cr:YSGG laser irradiation; Group2:2W-20Hz Er,Cr:YSGG laser irradiation; Group3:2,5W-10Hz Er,Cr:YSGG laser irradiation; Group4:2,5W-20Hz Er,Cr:YSGG laser irradiation; Group5: 3W-10Hz Er,Cr:YSGG laser irradiation; and Group6:3W laser-20Hz Er,Cr:YSGG laser irradiation. Each tooth hosted one test cavity prepared with one of the Er,Cr:YSGG laser irradiation and one control cavity prepared with a conventional diamond bur in a high-speed hand piece. Both cavities were placed at the cervical margin of the tooth and were restored and finished according to the manufacturer's instructions. All the restorations were subjected to thermocycling and load cycling. Microleakage was assessed using 0.5% basic-fuchsin solution and the specimens were sectioned longitudinally in buccolingual direction. Dye penetration was scored based upon the extent of the dye using a stereo-microscope. The data were analyzed using the Kruskal-Wallis and Wilcoxon Signed Ranks Test. Results: There were no statistically significant differences in microleakage (p>0.05) at either enamel or dentine margins among experimental groups. Lased groups resulted with statistically significant less microleakage compared to controls at both enamel and dentine margins in Groups 4 and 6 (p<0.05). Conclusions: 2,5W-20Hz and 3W-20Hz Er,Cr:YSGG laser irradiation may be an alternative to the conventional diamond bur for prevention of microleakage of compomer restorations.